TAFA’UL TRADITION IN CLASSICAL TURKISH LITERATURE AND REFLECTION OF TAFA’UL ON POETRY - Melek DİKMEN (Fırat University, 2019)
Islam have changed and converted the Turks from the point of sociality, culture and literature. In the Islamic culture and civilization, Arabs and Persians are together with them. While writing their poems, poets have taken advantage of the elements that belong to common Islamic Civilization besides national elements and they have been affected by each other. One of the qualities that the poets have been affected is tafa’ul tradition whose reflections have sometimes been seen in Ottoman Poetry. While doing tafa’ul, Ottoman poets used Fuzuli, Atayi, Hayali’s Diwans, Persian poets’ works such as Hafiz, Orfi and Enveri’s Diwans, Sa’di-i Shirazi’s Gulistan and especially the Holy Qoran. In this study, a brief information about tafa’ul tradition will be given and which books the Turkish poets used in tafa’ul tradition will be dealt.